MOOCs IN RUSSIAN UNIVERSITIES - Svetlana V. Titova (Высшее образование в России)
MOOCs are becoming increasingly popular all over the world and the means by which learning is measured, evaluated, and accredited has become topic of controversy in higher education. The objective of this paper is to investigate the models of massive online open courses, their technological, administrative and methodological peculiarities. The best samples of foreign and Russian projects on MOOCs are highlighted and analyzed. MOOCs will continue to play a major role in the rapid evolution of higher education so it is necessary to analyze and put into practice of Russian universities and colleges the pedagogical potential provided by this new educational phenomenon.